Weekend courses on ultrasonography as a form of teaching knowledge and the skills necessary to perform ultrasounds in the family physician’s practice - Szwamel, Katarzyna; Polański, Piotr; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
Background . Growth in ultrasound use by non-radiologists has outpaced radiologist-performed ultrasound in the last decade. Poland has a well-organized system of teaching ultrasonography. Objectives . To establish whether family physicians, after completion of weekend courses on ultrasound abdominal cavity imaging, recommend this form of training. To identify main reasons for family physician to attend training in USG, their preferences regarding the form of such courses and the difficulties most often faced by family physicians when performing a USG. Material and methods . This survey-based study using the authors’ own questionnaire was conducted in March 2016 among 81 primary care physicians who had completed weekend courses on ultrasound abdominal cavity imaging. Results . The main reasons why family physicians participated in ultrasound courses were the possibility of expanding knowledge (50.7%) and quicker patient diagnosis (20%). According to the respondents, difficulties with performing an ultrasound resulted mainly from their insufficient knowledge of anatomy (41.30%), technical problems (32.61%) and a lack of spatial imagination (28.26%). Organs that family physicians found especially difficult to diagnose were the retroperitoneal space (40%) and pancreas (36%). The majority of participants (86.36%) would recommend weekend ultrasound courses. Conclusions . Family physicians participate in ultrasound courses mostly for economic reasons. Intensive weekend training is enough to gain the knowledge necessary to perform an ultrasound examination. A crucial element of physicians’ ultrasound education is two week’s work on a provided ultrasound scanner in a primary care center. More time should be devoted to teaching a USG examination of the retroperitoneal space and the pancreas, as well as spatial imagination training.